2009
DOI: 10.1177/082585970902500302
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and needs of Bereaved Carers during Palliative and End-Of-Life Care for People with Chronic Obstructive Pulmonary Disease

Abstract: Aim: This study explored the experiences of palliative care that bereaved carers had while providing care to a dying loved one with chronic obstructive pulmonary disease (COPD). Method: Semi-structured interviews were undertaken with nine carers who had lost a loved one in the preceding 6 to 24 months. These interviews explored levels of satisfaction with disease management, symptom management, and end-of-life care. With permission, interviews were tape recorded, transcribed, and subjected to content analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 16 publications
0
77
0
1
Order By: Relevance
“…In qualitative studies, spousal caregivers of people with advanced COPD have discussed the burden of caring [7,10] and have reported fatigue, loss of concentration and lack of sleep [19]. They have described restrictions on their own lives [6,7,24-26], isolation [6,24,26], anxiety and emotional distress [6,7,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In qualitative studies, spousal caregivers of people with advanced COPD have discussed the burden of caring [7,10] and have reported fatigue, loss of concentration and lack of sleep [19]. They have described restrictions on their own lives [6,7,24-26], isolation [6,24,26], anxiety and emotional distress [6,7,24].…”
Section: Discussionmentioning
confidence: 99%
“…They have described restrictions on their own lives [6,7,24-26], isolation [6,24,26], anxiety and emotional distress [6,7,24]. They have reported a lack of information about the prognosis and future management of the condition [24], a lack of practical information and information about services [24], a lack of emotional and bereavement support, and a lack of respite services [10]. The review by Caress et al concluded there is a dearth of information on the needs of caregivers of people with COPD and interventions that may best support them [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, health professionals were seen to provide sporadic information [35,36], use language that was too technical or clinical thus limiting patient and caregiver’s ability to be involved in their own care [37], use euphemisms that weakened understandings of the health issues at hand [38], and provide conflicting information and approaches regarding treatments [38]. This lack of specific information or failure to explain information in clear terms was linked to greater patient anxiety as well as strain on caregivers, leading to mismanagement of symptoms and thus increased patient hospitalizations [32,34,39].…”
Section: Resultsmentioning
confidence: 99%